Philosophical and Legal Basis of Territorial Self-Governance - Katarzyna Doliwa; Adam Doliwa (Barometr Regionalny, 2019)
The subject of the article are selected philosophical and fundamental legal (i.e., systemic and constitutional, foundations of self-governance and local democracy). The authors present a general concept and the most important pragmatic function of democracy. The subject of the analysis is also the legal principle of self-governance as a systemic postulate of the democratic state ruled by law. The theoretical inspiration for the deliberations on decentralization and local democracy are the philosophical and political concepts of Ostrom and the philosophical classics: Hobbes, Montesquieu, and de Tocqueville. Self-governance and democracy, also considered from the point of view of their merits and disadvantages, have been included as a counterweight to centralism and monocentric democracy carrying a number of threats to freedom. In order to illustrate general arguments based on the method of analysis of normative and philosophical texts, the authors also use the example of American local democracy; it was chosen as a form of self-governance and local democracy in a modern sense, yet the oldest one and very well-functioning in practice. In the conclusions, the authors state what territorial self-governance is and what role it plays in the democratic system. They also emphasize that territorial self-governance, through actual decentralization of public authority, ensures democracy and secures against the transformation of monocentric democracy into a dangerous oligarchy.